ISLAMIC COMMUNITIES DEVELOPMENT STRATEGY IN UMAR BIN KHATAB ERA - Samsinas, Samsinas (State Islamic University of Datokarama Palu, 2022)
Umar bin Khatabis well-known as a leader with great attention to develop Muslim society welfare in term of social and economic. Musli community in his leadership era enjoyed high properity due to Umar bin Khatab economic policy. However, limited is known how Umar bin Khatab managed Muslim society welfare during his leadership period. This study, therefore,discusses the Islamic community development approach during the time of Umar bin Khatthabra. Is the result of library research from various sources. The study uses a professional approach that refers to efforts to increase independence and improve the service system within the framework of social relations. Furthermore, the radical approach refers to efforts to change the imbalance of social relations through empowering weak groups. Umar has implemented various policies related to the empowerment of the Islamic community during umar’s leadership. In addition to fiscal policy as well as economic empowerment in the form of providing pension benefits and social security, Umar also provided opportunities for Muslims to utilize zakat money and spoils of war in a distribution according to Islamic law. Establish baitulmaal, build markets and market systems without usury 'as the economic center of the Islamic community and other things that are also empowered to realize an ongoing development system.